Culturally Adapted Cognitive Behavioral Therapy for Moderate Depression and Non-Suicidal Self-Injury Patients - Kumar, Anand; Hyder Shaikh, Irsa; Sher, Zainab; A Malik, Mareen (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to evaluate the effectiveness of culturally adapted cognitive behavioral therapy (CA-CBT) for treating moderate depression and NSSI in Pakistani patients. Methods: A randomized controlled trial was conducted with 100 participants aged 18-35 years, diagnosed with moderate depression and engaging in NSSI behaviors. Participants were randomly assigned to either the CA-CBT intervention group (n=50) or the standard care control group (n=50). The CA-CBT program integrated Islamic teachings and cultural practices with conventional CBT techniques. Depression and NSSI behaviors were assessed at baseline, post-treatment, and a 3-month follow-up using the Beck Depression Inventory (BDI) and the Self-Injury Behavior Scale (SIBS). Results: The CA-CBT group showed significant reductions in depressive symptoms (p<0.001) and self-injurious behaviors (p<0.001) compared to the control group. Qualitative feedback indicated that participants in the intervention group found the therapy culturally and religiously meaningful, which enhanced engagement and reduced stigma associated with mental health care. Conclusions: The study demonstrates that culturally adapted CBT is an effective intervention for treating moderate depression and NSSI in Pakistani patients. Integrating cultural and religious elements into therapy enhanced treatment adherence and outcomes, suggesting that CA-CBT could be a valuable approach in non-Western, Muslim-majority countries.